Feasibility and Safety of a Modified Outpatient Regimen With Intravenous/Intraperitoneal Chemotherapy for Optimally Debulked Stage III Ovarian Cancer. Issue 2 (February 2015) - Bruixola, Gema; Domingo, Santiago; Díaz, Roberto; Caballero, Javier; Palomar, Laura; De La Cueva, Helena; Santaballa, Ana
<x xml:space="preserve">Abstract</x> Objective Intraperitoneal (IP) chemotherapy improves survival in optimally debulked ovarian cancer patients. However, the need for inpatient administration and the perceived higher toxicity rates compared with standard intravenous chemotherapy have limited its widespread application. Several modified outpatient schemes, such as the Spanish Ovarian Cancer Research Group (GEICO) regimen, have been tested and have reported overall better tolerance with an improvement in completion treatment rates. The aim of our study was to assess the toxicity of the GEICO regimen in patients treated at our institution. Methods We reviewed clinical records of stage III ovarian cancer patients with optimally debulked primary cytoreduction surgery that were treated from June 2009 to April 2013 with the GEICO regimen. Patients received intravenous paclitaxel (175 mg/m2) for 3 hours on day 1, IP cisplatin (100 mg/m2) on day 2, and IP paclitaxel (60 mg/m2) on day 8 every 21 days for a maximum of 6 cycles. Results Twenty-one patients were identified. In 67% of the patients, IP port placement was performed at the primary surgery. The most common grade 3-to-4 toxicities seen were abdominal pain (14.3%) and neurotoxicity (9.5%). Eighteen patients (85.7%) completed the 6 cycles. Three patients stopped chemotherapy because of treatment-related toxicity. There were no serious port-related complications. With a median follow-up of 46 months, median progression-free survival was 23 months (95% confidence interval [11.8–34.6]). Nine patients (42.9%) have relapsed; most relapses were multifocal and extraperitoneal. Conclusion The administration of the GEICO outpatient modified regimen was feasible with a good safety profile. It seems to show less toxicity than previously reported IP chemotherapy regimens. In our institution, port-related complications were infrequent and easily managed. However, further studies are warranted to establish the optimal IP regimen in a prospective manner and to validate it in a larger phase 3 trial.